Maribor v 13. stoletju - Ravnikar, Tone (Studia Historica Slovenica, 2020)
The author re-analysed the documentary material and compared the possessive structures to a certain extent with the newly arranged relations between the noble families in and around Maribor. The comparison showed that the nobles of Maribor, Viltuš and Limbuš were undoubtedly related to each other. The same is true for the nobles of Melje and Hompoš, but it is very likely that the Maribor-Viltuška and Hompoško-Meljska branches were much more closely connected at the beginning of the 13th century than was assumed.
Keywords: history of Maribor; Maribor; middle ages; nobility; plemiške rodbine; plemstvo; srednji vek; zgodovina